2021
DOI: 10.3390/en14227783
|View full text |Cite
|
Sign up to set email alerts
|

Energy, Environmental, and Economic Analyses of a District Heating (DH) Network from Both Thermal Plant and End-Users’ Prospective: An Italian Case Study

Abstract: District heating (DH) is an alternative technology to Individual Heating (IH) for satisfying end-user’s needs. This paper assesses the competitiveness of a DH network in the center of Italy from energy, environmental, and economic points of view considering both thermal power plant and end-users’ sides. On the thermal power plant side, the energy analysis considers the Primary Energy Saving (PES) and the specific energy (Esp) of the fuel actually exploited in the thermal power plant compared to its Low Heating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Finally, literature studies usually relate to the thermal network or relate to the user side (i.e., the building). To this respect, an exception is made in [26], where an Italian district heating network has been analysed (from both thermal plant and end-users' perspectives) considering energy, environmental and economic aspects; however, it does not include a detailed modelling of the network.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, literature studies usually relate to the thermal network or relate to the user side (i.e., the building). To this respect, an exception is made in [26], where an Italian district heating network has been analysed (from both thermal plant and end-users' perspectives) considering energy, environmental and economic aspects; however, it does not include a detailed modelling of the network.…”
Section: Introductionmentioning
confidence: 99%
“…Among different technologies for recovering geothermal energy, a ground source heat pump (GSHP) is one of the most energy-efficient, environmentally clean, and cost-effective systems available with a long life span and high energy conversion rate into a heating and cooling system [10]. Spitler et al [11] reported the technical benefits of ground source heat pumps and showed that it could be a promising option for improving the sustainability within the building.…”
Section: Introductionmentioning
confidence: 99%
“…The modelling of DHC networks is often seen in the published literature, featuring a diverse array of objectives. Performance assessment, from different points of view, was the main topic of the study by Corradi et al [4]. Primary energy savings, the amount of CO 2 avoided, and economic indicators were computed for a DH network, in Central Italy, characterized by multiple technologies and energy vectors.…”
mentioning
confidence: 99%